THE URGENCY OF PROGRESSIVISM IN ACADEMIC FREEDOM-BASED EDUCATION - Fitria Dewi Navisa; Sintiya Dewi Patmalasari; Della Lara Audia (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2022)
Every country will certainly do everything possible to maintain the integrity and progress of the country. The nation's generation is the most valuable asset because every individual has the best potential and ability should be cared for and maintained by its potential by providing good education. Education is a program that moves to add scientific insight and has a huge influence for the progress of the times. Education is built from various schools of educational philosophy that apply from time to time. One of them is widely used today, namely the flow of progressivism philosophy. Progressivism has the idea that education should focus on the development of students, not on educators. The flow of progressivism education philosophy teaches independent learning so that students are able to survive and create solutions for all situations that may occur in the future. An educator is not only tasked with conveying the knowledge he has in the classroom but is also obliged to assist students in developing every best potential they have. This research was conducted by using a literature study. The approach used in this paper is a quantitative research approach with descriptive methods and comparative approaches. Academic freedom is an educational system that instills humanist and democratic education. Education based on academic freedom is carried out by means of mutual openness between educators and students. Academic freedom that departs from the flow of progressivism prohibits educators from demanding and limiting the thinking area of students. Educators and students have the same right to explore knowledge and express their opinions. In essence, educators are companions and facilitators for the learning process of students.